Analisis Hukum terhadap Praktik Manipulasi Harga Bahan Pokok di Pasar Cik Puan Pekanbaru - Salsabila Adira Balqis (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This study analyzes the practice of staple food price manipulation at Cik Puan Market in Pekanbaru, which is alleged to be carried out by a group of traders through stockpiling, supply coordination, and price regulation that could potentially cause market distortions. This phenomenon has led to unreasonable price increases in strategic commodities such as chili, onions, rice, cooking oil, and chicken, thereby negatively affecting consumers and regional economic stability. This research uses a normative juridical approach with descriptive qualitative analysis methods, supported by empirical data from local government reports, official news, and findings from trade department supervision. The results of the study indicate that these price manipulation practices are in violation of Articles 5, 11, and 19 of Law No. 5 of 1999 about Consumer Protection. This study emphasizes that the weak supervision of the supply chain in traditional markets, as well as the minimal coordination between agencies, causes price manipulation practices to continue repeatedly. It is necessary to strengthen law enforcement, ensure transparency in the distribution of basic necessities, and enhance the role of local governments and the KPPU in order to create stable, competitive, and fair prices for the public.